Influence of physical and geometrical parameters on electrical properties of short gate GaAs MESFETs - Khemissi, S.; Merabtine, N.; Zaabat, M.; Kenzai, C.; Saidi, Y.; Amourache, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
In the information sciences such as computer science, telecommunications, the treatment of signal or image transmission, the field effect components play an important role. In the frame of our work, we are interested in the study of the gallium arsenide short gate field effect transistor called GaAs MESFET. After analytical studying the component static characteristics, according to different operation regimes, a numerical simulation was worked out. The influence of technological dimensions (L, Z, a, and Nd) was studied. The obtained results allow us to determine optimal parameters of the devices from the viewpoint of their applications and specific use.